The mouse dorsal skinfold chamber as a model for the study of thrombolysis by intravital microscopy - Boulaftali, Yacine; Lamrani, Lamia; Rouzaud, Marie-Catherine; Loyau, Stéphane; Jandrot-Perrus, Martine; Bouton, Marie-Christine; Ho-Tin-Noé, Benoît (Thrombosis and Haemostasis, 2012)
Although intravital microscopy models of thrombosis in mice have contributed to dissect the mechanisms of thrombus formation and stability, they have not been well adapted to study long-term evolution of occlusive thrombi. Here, we assessed the suitability of the dorsal skinfold chamber (DSC) for the study of thrombolysis and testing of thrombolytic agents by intravital microscopy. We show that induction of FeCl3-induced occlusive thrombosis is achievable in microvessels of DSCs, and that thrombi formed in DSCs can be visualised by intravital microscopy using brightfield transmitted light, or fluorescent staining of thrombus components such as fibrinogen, platelets, leukocytes, and von Willebrand factor. Direct application of control saline or recombinant tissue-plasminogen activator (rtPA) to FeCl3-produced thrombi in DSCs did not affect thrombus size or induce recanalisation. However, in the presence of hirudin, rtPA treatment caused a rapid dose-dependent lysis of occlusive thrombi, resulting in recanalisation within 1 hour after treatment. Skin haemorrhage originating from vessels located inside and outside the FeCl3-injured area was also observed in DSCs of rtPA-treated mice. We further show that rtPA-induced thrombolysis was enhanced in plasminogen activator inhibitor-1-deficient (PAI-1−/−) mice, and dropped considerably as the time between occlusion and treatment application increased. Together, our results show that by allowing visualization and measurement of thrombus lysis and potential bleeding complications of thrombolytic treatments, the DSC provides a model for studying endogenous fibrinolysis and for first-line screening of thrombolytic agents. Furthermore, using this system, we found that thrombin and clot aging impair the thrombolytic action of rtPA towards FeCl3-produced thrombi.
Keywords: Dorsal skinfold chamber; intravital microscopy; thrombolysis; thrombosis; tPA